Fennel and Rue - Howells, William Dean, 1837-1920 (Salt Lake City, UT : Project Gutenberg, 2004)
"Fennel and Rue" by William Dean Howells is a novel written during the late 19th century. The story follows the character Philip Verrian, an author struggling to gain recognition for his work, as he deals with the complexities of fame, the literary world, and personal relationships while grappling with the unexpected correspondence from an admirer who writes to him about his serialized story. At the start of the novel, we are introduced to Verrian's experience of finally achieving success after a long struggle for acceptance from editors, specifically through his serial publication in a magazine. This victory is marred by a letter he receives from a girl who, despite claiming to be a dying invalid, asks him to share the ending of his story. Following this correspondence, Verrian consults with his editor regarding the appropriateness of responding to her request. The letters become a source of tension, reflecting the intricacies of author-reader relationships and Verrian's own insecurities about his writing and identity. The opening of the novel sets the stage for themes of ambition, literary ethics, and the nature of romantic attraction amid the backdrop of literary fame. (This is an automatically generated summary.)
Release date is 2004-10-24
Produced by David Widger
Keywords: Editors -- Fiction; Novelists -- Fiction; Fan mail -- Fiction